Extracellular ATP hydrolysis in Caco-2 human intestinal cell line - Schachter, Julieta (2021)
Extracellular nucleotides and nucleosides activate signaling pathways that play major roles in the physiology and pathophysiology of the gastrointestinal tract. Ectonucleotidases hydrolyze extracellular nucleotides and thus regulate ligand exposure to purinergic receptors. In this study, we investigated the expression, localization and activities of ectonucleotidases using Caco-2 cells, a model of human intestinal epithelial cells. In addition, by studying ATP release and the rates of extracellular ATP (eATP) hydrolysis, we analyzed the contribution of these processes to the regulation of eATP in these cells. Results show that Caco-2 cells regulate the metabolism of eATP and by-products by ecto-nucleoside triphosphate diphosphohydrolase-1 and -2, a neutral ecto-phosphatase and ecto-5′-nucleotidase. All these ectoenzymes were kinetically characterized using intact cells, and their presence confirmed by denatured and native gels, western blot and cytoimmunofluorescence techniques. In addition, regulation of eATP was studied by monitoring the dynamic balance between intracellular ATP release and ectoATPase activity. Following mechanical and hypotonic stimuli, Caco-2 cells triggered a strong but transient release of intracellular ATP, with almost no energy cost, leading to a steep increase of eATP concentration, which was later reduced by ectoATPase activity. A data-driven algorithm allowed quantifying and predicting the rates of ATP release and ATP consumption contributing to the dynamic accumulation of ATP at the cell surface.